2020
DOI: 10.1111/clr.13691
|View full text |Cite
|
Sign up to set email alerts
|

Periimplant bone changes in different abutment heights and insertion timing in posterior mandibular areas: Three‐year results from a randomized prospective clinical trial

Abstract: Aim To compare the influence of the abutment height and its insertion timing on the marginal bone change (MBC) variation of implants placed at posterior mandibular partial edentulous areas in a medium follow‐up period. Material and methods This randomized clinical trial (RCT) comprised a sample of patients with posterior mandibular edentulous areas, treated with at least two implants and distributed into three groups: implants connected to a 2 mm height abutment during the surgical stage (Group A); implants co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…According to the results from the two previous trials (Gothberg et al, 2018; Todisco et al, 2018) and from the results published by Toia, Stocchero, Becktor, et al (2019), the MBL change is more evident in the first year of loading. During the first year, peri‐implant bone remodelling might be influenced by several factors, such as surgical procedures, the number of surgical stages, repetitive disconnections during prosthetic procedures, the type of implant connection, and the formation of supracrestal tissue (Borges et al, 2018; Borges et al, 2020; Qian et al, 2012). One explanation of the differences in MBL in this study compared with other trials may be the type of implant‐abutment connection, which may initiate different responses, particularly during the first year of loading (Astrand et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results from the two previous trials (Gothberg et al, 2018; Todisco et al, 2018) and from the results published by Toia, Stocchero, Becktor, et al (2019), the MBL change is more evident in the first year of loading. During the first year, peri‐implant bone remodelling might be influenced by several factors, such as surgical procedures, the number of surgical stages, repetitive disconnections during prosthetic procedures, the type of implant connection, and the formation of supracrestal tissue (Borges et al, 2018; Borges et al, 2020; Qian et al, 2012). One explanation of the differences in MBL in this study compared with other trials may be the type of implant‐abutment connection, which may initiate different responses, particularly during the first year of loading (Astrand et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results from the two previous trials (Gothberg et al, 2018;Todisco et al, 2018) and from the results published by , the MBL change is more evident in the first year of loading. During the first year, peri-implant bone remodelling might be influenced by several factors, such as surgical procedures, the number of surgical stages, repetitive disconnections during prosthetic procedures, the type of implant connection, and the formation of supracrestal tissue (Borges et al, 2018;Borges et al, 2020;Qian et al, 2012).…”
Section: Radiographic Parametersmentioning
confidence: 99%
“…1 One of the most important prerequisites for success of the implant therapy is alveolar bone stability, which depends on the quality of biological integration with bone, also known as osseointegration. 2 Early marginal bone loss (MBL) around implants has been attributed to several factors, including but not limited to implant collar design; microgaps and movements 3 ; implant-abutment junction vertical position 4 ; abutment height 5 ; implant crown/restoration design 6 ; trauma induced by flap elevation 7 ; reduced buccal bone and soft tissue thickness at the implant site 8 ; and possible inflammatory reactions. 9 Additionally, initial bone resorption is expected to occur during the formation of supracrestal fiber height (e.g., biologic width) consisting of the epithelial and connective tissue adhesion forming a mucosal barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the retrospective nature of their study, these results might have been confounded by the thickness of the soft tissue. However, several randomized clinical trials have since confirmed that abutment height has a significant influence on early bone loss, irrespective of the thickness of the soft tissue, therefore meaning that abutments with a height of 1 mm should be avoided (Blanco et al, 2018; Borges et al, 2021; Pico et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the timing of the abutment insertion and the fact that it is no longer disconnected are other factors that seem to have an influence on MBL. Borges et al (2021) compared this factor in a randomized prospective clinical trial with a sample size of 59 implants in 29 patients. A significantly lower MBL was detected when the abutment was installed immediately after implant placement (1 stage) than when the abutment was installed 2 months after the implant had been placed (2 stages).…”
Section: Discussionmentioning
confidence: 99%